As comunidades tradicionais do Parque Nacional dos Lençóis Maranhenses: um estudo sobre os antigos e os novos conflitos que estão se estabelecendo - Castro, Regis Vercauteren de Souza (2020)
Throughout history, natural resources have been used in an uncontrolled manner, without any concerns about their finitude. With the start of society for the exhaustion of these resources, it was necessary to conserve biodiversity, this occurred through the creation of Conservation Units. UC's are managed in Brazil by the National System of Conservation Units (SNUC), which through ICMBio and IBAMA create, manage and maintain these UC's. Except for the fact that these protected areas guarantee the maintenance, conservation and protection of biodiversity, many of them were created in offices and have brought with them problems and conflicts since the moment of their creation, since the realization of these areas did not take into account that there were people residing within these locations for centuries, developing their traditional way of life geared to their livelihood, thus transforming this area into a place with socio-environmental exclusions and conflicts. This exclusionary model of conservation calls for the removal of any resident residing within these UC's, especially those of Integral Protection, such as the Lençóis Maranhenses National Park (PNLM), which has about 17 communities within the territory, which develop conflicting activities such as agriculture , livestock, fishing, but destined for their subsistence. Since the creation of the PNLM, these communities have suffered from the limitations to their traditional land use imposed by legislation through ICMBio. As most of the time these protected areas are linked to beautiful natural landscapes, the tourist exploitation of these areas takes place, being a factor that brings with it several other models of conflicts such as: more expropriation of populations, contradictions between these communities, real estate speculation among others . With the PNLM of Lençóis Maranhão, we can identify all the problems that happen within a UC that has traditional communities. However, the tourist capital is increasingly aiming to take over this Conservation Unit, currently two projects have the intention of transforming the area into a major tourist pole, linking it to two other Conservation Units that extend through Maranhão, Piauí and Ceará, one of the projects is the Federal Senate Bill 465/2018 which aims to reduce the limits of the Park for the exploration of activities related to Tourism in the region, excluding traditional communities from the limits of the Park and the other process that is already underway. progress is to grant it to the private sector. The problem is that neither the problems that always occur within the UC's, such as the resettlement of these populations, have never been resolved, now others arise that will lead to a more intensive worsening of the traditional communities there.